72=(x-1)(x)(x+9)

Simple and best practice solution for 72=(x-1)(x)(x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 72=(x-1)(x)(x+9) equation:


Simplifying
72 = (x + -1)(x)(x + 9)

Reorder the terms:
72 = (-1 + x)(x)(x + 9)

Reorder the terms:
72 = (-1 + x) * x(9 + x)

Reorder the terms for easier multiplication:
72 = x(-1 + x)(9 + x)

Multiply (-1 + x) * (9 + x)
72 = x(-1(9 + x) + x(9 + x))
72 = x((9 * -1 + x * -1) + x(9 + x))
72 = x((-9 + -1x) + x(9 + x))
72 = x(-9 + -1x + (9 * x + x * x))
72 = x(-9 + -1x + (9x + x2))

Combine like terms: -1x + 9x = 8x
72 = x(-9 + 8x + x2)
72 = (-9 * x + 8x * x + x2 * x)
72 = (-9x + 8x2 + x3)

Solving
72 = -9x + 8x2 + x3

Solving for variable 'x'.

Reorder the terms:
72 + 9x + -8x2 + -1x3 = -9x + 9x + 8x2 + -8x2 + x3 + -1x3

Combine like terms: -9x + 9x = 0
72 + 9x + -8x2 + -1x3 = 0 + 8x2 + -8x2 + x3 + -1x3
72 + 9x + -8x2 + -1x3 = 8x2 + -8x2 + x3 + -1x3

Combine like terms: 8x2 + -8x2 = 0
72 + 9x + -8x2 + -1x3 = 0 + x3 + -1x3
72 + 9x + -8x2 + -1x3 = x3 + -1x3

Combine like terms: x3 + -1x3 = 0
72 + 9x + -8x2 + -1x3 = 0

The solution to this equation could not be determined.

See similar equations:

| 7X+5.5Y=119 | | sqrt-7x+5=sqrt-3x+9 | | 3n-6n=-15 | | 4y-13= | | 4y+38=20+8y | | 2(x+15)=x+21 | | y(49/60)=(7/2) | | x+15=x+21 | | =ln(0.5x^2) | | ((x^2)+y)dx=-xdy | | 6(2n-2)=(8n+8)+1 | | a=1/2bc2 | | (5x-14)+90+y=180 | | 3n-1=-28 | | 4a+8=2a | | 5m-1=14 | | 5L-12=38 | | (2x+13)+3x+57=180 | | -k+5=24 | | -8j-59=13 | | 5*x+57= | | 14i-5=-33 | | 14I-5=-93 | | 3(x-2)+2x=7-(x+5) | | (2c-3)(2c+4)(2c-1)=0 | | 70=(x*x+2*2) | | -12g-4=44 | | -10m+8=-8 | | (x^2+9x+4)=0 | | 6(x-5)=50-4x | | 19f+36=112 | | 5m+7m=17 |

Equations solver categories